Effective Decontamination and Regeneration Protocol for in vitro Culture of Strawberry Cv. Chandler - S Diengngan (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2014)
Nodal segments of strawberry cv. Chandler were collected from the field and surface sterilization of the explants was carried out using various levels of decontaminants as different treatments viz. sodium hypochlorite (NaClO) 0.5% for 7, 5 and 3 min and mercuric chloride (Hg Cl2) 0.1% for 5 min, 3 min and 3 min 10 sec. The explants were excised and cultured for 3 weeks on the initiation medium supplemented with various levels of BAP (0.5, 1, 1.5 and 2mg/l) and its combination with GA (0.5 and 1mg/l). Sub culturing was done and finally rooting was initiated on the medium supplemented with various levels of IBA (0.5, 1, 1.5 and 2mg/l) for 4 weeks. The results obtained indicated that, among the decontaminants, treatment of explants with Hg Cl2 0.1% for 3 min 10 sec resulted in the minimum contamination and browning of explants. Further, maximum shoot proliferation percentage, shoots per explant and minimum number of days to shoot initiation was observed when explants were cultured on MS medium supplemented with 1.5 mg/l BAP over other concentrations of either BAP or in combination with GA. However, the maximum length of shoots was obtained in medium supplemented with 1.5 mg/l BAP + 0.5 mg/l GA. While, medium supplemented with 0.5 mg/l IBA supported highest percentage of rooting, the highest number of roots, maximum root length of microcuttings and minimum number of days to root initiation were observed in medium supplemented with 1mg/l of IBA.